2016
DOI: 10.1016/j.pneurobio.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of gene–environment interaction in schizophrenia: A dimensional perspective

Abstract: Schizophrenia has long been considered as a disorder with multifactorial origins. Recent discoveries have advanced our understanding of the genetic architecture of the disease. However, even with the increase of identified risk variants, heritability estimates suggest an important contribution of non-genetic factors. Various environmental risk factors have been proposed to play a role in the etiopathogenesis of schizophrenia. These include season of birth, maternal infections, obstetric complications, adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 458 publications
(418 reference statements)
0
50
0
Order By: Relevance
“…Separating these genetic from environmental influences is quite difficult. Most co‐factors may be environmental in nature, and include effects of stressful life events, prenatal infections, perinatal hypoxia, or substance abuse which are known risk factors for schizophrenia [van Os et al, ; Schmidt‐Kastner et al, ; Ayhan et al, ]. Also genetic epistasis between variants may be a relevant factor [Sadee et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Separating these genetic from environmental influences is quite difficult. Most co‐factors may be environmental in nature, and include effects of stressful life events, prenatal infections, perinatal hypoxia, or substance abuse which are known risk factors for schizophrenia [van Os et al, ; Schmidt‐Kastner et al, ; Ayhan et al, ]. Also genetic epistasis between variants may be a relevant factor [Sadee et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…MIA appears to act as a “disease primer”(14) to make an individual more susceptible to the effects of genetic mutations and environmental exposures in triggering disease-related symptoms later in life(41). Consistent with this idea, the incidence of both ASD and SZ is much higher in families with autoimmune disorders(2, 6) and the effect of maternal infection in increasing SZ risk is greater in families with a history of SZ(3).…”
Section: Mia As a Disease Primermentioning
confidence: 99%
“…Intriguingly, an analysis in a relatively small cohort of the interaction between polymorphism in sialyltransferase (ST8SIA2), a susceptibility gene for schizophrenia, and the incidence of stressful life events showed a trend toward a certain amount of stress being protective against the disorder (Mandelli et al, 2016). An increasing number of human and animal studies have found interacting effects of genetic mutations and environmental factors (including MIA) on the manifestation of schizophrenialike symptoms (Ayhan et al, 2016). An increasing number of human and animal studies have found interacting effects of genetic mutations and environmental factors (including MIA) on the manifestation of schizophrenialike symptoms (Ayhan et al, 2016).…”
Section: Schizophreniamentioning
confidence: 99%
“…A recent study showed a genetic association of schizophrenia with allelic variants of complement component C4, a protein involved in an innate immune system pathway that rapidly recognizes and eliminates pathogens and cellular debris (Sekar et al, 2016). An increasing number of human and animal studies have found interacting effects of genetic mutations and environmental factors (including MIA) on the manifestation of schizophrenialike symptoms (Ayhan et al, 2016).…”
Section: Schizophreniamentioning
confidence: 99%